Pengukuran Kualitas Layanan Website Dinas Pendidikan Kota Malang Dengan Menggunakan Metode Webqual 4.0 dan IPA - Amirah Al Baiti; Suprapto Suprapto; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Website is an important part of information technology. We can not deny that the role of thewebsite is essential in almost all aspect of life, especially for an organization or company, including thegovernment. Education Department of Malang is one of many goverment agency that implement awebsite. But since 2008 Education Department of Malang website evaluation has not been done so theydon't have any idea which is the website have a good quality or not and the website get a lot complainabout unattractive design and uneffective feature. This study analyzes and measures the service qualityof Education Department of Malang website from enduser point. User data obtained by distributingquestionnaires based on three dimensions at WebQual 4.0 the dimensions of usability, information andservice interaction. Then the results of the questionnaire were analyzed by Importance PerformanceAnalysis (IPA). The analysis showed that Malang Department of Education website does not complywith the expectations of users with the results of analysis of suitability of 94.43% or <100% and theaverage yield gap analysis of-0.1675 or <0. Priority improvement on this website are the attributes ofnumber 9, 13 and 16, which is an attribute in Quadrant A.